Improvement of the Deep UV Sensor Performance of a β-Ga2O3Photodiode by Coupling of Two Planar Diodes - Vieira, Douglas H. [UNESP]; Badiei, Nafiseh; Evans, Jonathan E.; Alves, Neri [UNESP]; Kettle, Jeff; Li, Lijie (Institute of Electrical and Electronics Engineers (IEEE), 2020)
$\beta $ -Ga2O3 is one of the promising semiconductor materials that has been widely used in power electronics and ultraviolet (UV) detectors due to its wide bandgap and high sensitivity to UV light. Specifically, for the UV detection application, it has been reported that the photocurrent was in the scale of microamps ( $\mu \text{A}$ ), which normally requires sophisticated signal processing units. In this work, a novel approach based upon coupling of two Schottky diodes is reported, leads to a substantial increase in photocurrent (186 times) when benchmarked against a conventional planar UV photodiode. The detectivity and responsivity of the new device have also been significantly increased; the rectification ratio of this device was measured to be $1.7\times 10^{7}$ with ultralow dark current, when measured in the reverse bias. The results confirm that the approach of coupling two Schottky diodes has enormous potential for improving the optical performance of deep UV sensors.
Keywords: Deep ultraviolet (UV); gallium oxide; performance improvement; photodetector; Schottky diode